Acid-corrosion-resistant crushing tool bit for crushing blast furnace titanium slag and preparation method of acid-corrosion-resistant crushing tool bit

By using acid-resistant alloy cutter heads composed of chromium, vanadium, tungsten and other elements, combined with high-temperature vacuum smelting and quenching treatment, the cutter head wear and corrosion problems in blast furnace titanium slag crushing is solved, achieving higher hardness and toughness, and extending The service life is improved and the crushing efficiency is improved.

CN119194289APending Publication Date: 2024-12-27恩宜瑞(江苏)环境发展有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411231186.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the blast furnace titanium slag crushing process, the blade head has aggravated wear due to high temperature and acidic environment, short service life and poor crushing effect.

Method used

Using acid-resistant alloy cutter heads composed of chromium, vanadium, tungsten, molybdenum, cobalt, manganese, titanium and iron, are prepared through vacuum smelting and casting processes, combined with surface quenching and low-temperature tempering to form high hardness and high toughness and wear-resistant cutter head.

Benefits of technology

It significantly improves the hardness, strength and corrosion resistance of the cutting head, extends the service life, and improves the crushing efficiency, avoiding cracks in the blade during the crushing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194289A_ABST
    Figure CN119194289A_ABST
Patent Text Reader

Abstract

The invention discloses an acid-corrosion-resistant crushing tool bit for crushing blast furnace titanium slag and a preparation method of the acid-corrosion-resistant crushing tool bit, and belongs to the technical field of tool bit manufacturing, the acid-corrosion-resistant crushing tool bit is composed of, by mass, 12.3% of Cr, 5.2% of V, 9.1% of W, 3.3% of Mo, 1.1% of Co, 4.5% of Mn, 5.2% of Ti, 0.5% of Si, 0.3% of C and the balance Fe, the acid-corrosion-resistant crushing tool bit comprises a tool body, and a plurality of tooth tool edges are integrally formed on the tool body. A preparation method of the crushing tool bit comprises the steps that all the components are put into a crucible to be heated and smelted to form a melt, and then casting, normalizing treatment, machining and heat treatment processes are conducted to obtain the crushing tool bit. And other elements can be tightly combined with iron, so that the crushing tool bit with high corrosion resistance, high hardness, high strength and high wear resistance is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cutter head manufacturing, and in particular to an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag and a preparation method thereof. Background Art

[0002] Blast furnace titanium slag is a by-product produced during the blast furnace smelting process, mainly composed of titanium dioxide (TiO 2 ) and iron oxide (FeO), and also contains magnesium, calcium, aluminum and other elements. The characteristic of this slag is that it contains a high proportion of TiO 2 , usually between 20% and 25%. The chemical composition and physical properties of blast furnace titanium slag make it potential for certain industrial applications.

[0003] The mechanical properties of blast furnace titanium slag include physical indicators such as hardness, compressive strength, and flexural strength. These properties determine the feasibility and treatment methods of blast furnace titanium slag in industrial applications. 2 By interacting with other oxides and silicates in the slag, acidic oxides are formed. These acidic oxides can form miscible solutions with other components in the slag, so that the blast furnace titanium slag presents an acidic environment.

[0004] When the existing crushing device crushes blast furnace titanium slag, the cutter head often suffers from aggravated wear due to the high temperature of continuous operation of the cutter head due to insufficient strength and hardness of the cutter head. In addition, the acidic environment of the blast furnace titanium slag corrodes the cutter head, which easily leads to a short service life of the cutter head and poor crushing effect. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag and a preparation method thereof.

[0006] The technical solution of the present invention is: an acid-resistant crushing cutter head for crushing blast furnace titanium slag, the acid-resistant crushing cutter head is composed of the following components in mass percentage: 12.3-18.7% Cr, 5.2-8.4% V, 9.1-11.6% W, 3.3-5.1% Mo, 1.1-3.2% Co, 4.5-6.8% Mn, 5.2-7.5% Ti, 0.5-0.8% Si, 0.3-0.5% C, and the balance is Fe.

[0007] Furthermore, the acid-corrosion-resistant crushing cutter head comprises a cutter body, a plurality of tooth cutting edges are integrally formed on the cutter body, and an engagement groove is formed between two adjacent tooth cutting edges.

[0008] Description: The titanium slag is crushed by the mutual engagement of two crushing cutter heads.

[0009] Furthermore, a method for preparing an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag comprises the following steps:

[0010] S1. Sprinkle C powder on the bottom of the crucible, then add Fe blocks, V particles, Cr particles, W powder, Mo powder, Co particles, Mn blocks, Ti particles into the crucible in sequence, then cover the surface of Ti particles with Si powder, and place the crucible in a vacuum melting furnace for vacuum melting;

[0011] S2. The vacuum melting furnace is first evacuated to 3-5Pa, and then filled with argon until the pressure in the vacuum melting furnace reaches 85-95kPa, and then the vacuum melting furnace is gradient heated. The temperature of the vacuum melting furnace is now raised to 1700-2000℃, and then maintained for 30-40min, and then raised to 2600-2800℃, and maintained for 20-30min. After the vacuum melting is completed, a melt is formed;

[0012] S3, introducing the high temperature melt into the crushing knife mold for casting, and after the casting is completed, naturally cooling and demoulding to obtain a crushing knife casting;

[0013] S4, placing the crushing knife casting into a vacuum heating furnace for normalizing treatment, and air cooling to 60-80° C. after the normalizing treatment to obtain a normalized casting;

[0014] S5, fixing the normalized casting on a lathe to perform surface turning on the meshing groove of the normalized casting by turning, and performing surface shoveling on the tooth edge of the normalized casting by a shoveling lathe, and obtaining a crushing cutter head machined part after the shoveling is completed;

[0015] S6. Heat-treating the machined parts of the crushing cutter head, and obtaining a finished crushing cutter head after the heat treatment is completed.

[0016] Furthermore, the average particle size of the Fe blocks and Mn blocks is 3-5 cm, the average particle size of the V particles, Cr particles, Co particles, and Ti particles is 1-3 mm, and the average particle size of the W powder, Mo powder, Si powder, and C powder is 40-80 μm.

[0017] Note: Fe and Mn blocks have low melting points and are easy to melt. Larger particle size can reduce costs. V particles, Co particles, and Ti particles have slightly higher melting points than Fe and Mn blocks. In order to mix the components evenly, their particle sizes are smaller than those of Fe and Mn blocks. The amount of Si powder added is small, and in order to make it more evenly distributed in the alloy, a smaller particle size is selected. C powder, W powder, and Mo powder have higher melting points, so they are added in the form of powder to make them better distributed in the alloy.

[0018] Furthermore, the casting speed is 8-10cm 3 / s, the melt temperature is 2600-2800℃ at the beginning of casting and greater than 2000℃ at the end of casting. After casting, the mold is naturally cooled to 20-40℃ and then demoulding begins.

[0019] Note: At the above casting speed, the alloy formed has less pores and slag, and the casting effect is good.

[0020] Furthermore, the normalizing temperature is 800-900°C, the normalizing holding time is 20-35min, the air cooling air temperature is 20-35°C, and the air flow rate is 3-4m / s.

[0021] Note: The above air cooling speed can effectively improve the internal stress of normalized castings, increase the plasticity and toughness of the material, and make it easier to machine.

[0022] Furthermore, the heat treatment is to perform surface quenching on the crushing cutter head machine. The specific method of the surface quenching is: place the workpiece in a vacuum heating furnace and heat it to 900-1000°C, maintain it for 5-10 minutes, and then place the crushing cutter head machined workpiece on the top of the quenching liquid box, rotate the crushing cutter head machined workpiece to quench only the meshing groove and the tooth cutter head, the quenching liquid level is 1-2 cm higher than the meshing groove, the quenching times are 2-3 times, and the finished crushing cutter head is obtained after quenching.

[0023] Description: Through surface quenching, the surface hardness of the tooth cutting edge and meshing groove is improved without destroying the toughness of other parts of the crushing cutter head, thereby improving the overall strength of the crushing cutter head and avoiding cracks in the blade body during the process of crushing titanium slag.

[0024] Furthermore, the heat treatment is to first immerse the crushing cutter head machined parts into quenching, and then perform low-temperature tempering treatment to obtain a finished crushing cutter head. The specific method of the immersion quenching is: place the crushing cutter head machined parts into a vacuum heating furnace and heat them to 900-1000°C, maintain them for 5-10 minutes, and then immerse the crushing cutter head machined parts in the quenching liquid for quenching. The quenching times are 2-3 times to obtain the quenched crushing cutter head.

[0025] Description: This method is to first quench the entire crushing cutter head to increase the overall hardness of the blade.

[0026] Furthermore, the low-temperature tempering treatment is to place the quenched crushing cutter head into a vacuum heating furnace and heat it to 250-300° C., maintain it for 10-15 minutes, and then cool it to 60-80° C. in the furnace to obtain a finished crushing cutter head.

[0027] Note: Low temperature tempering can improve the overall toughness of the blade and reduce its brittleness.

[0028] Furthermore, the low-temperature tempering treatment is to put the quenched crushing cutter head into a vacuum heating furnace, evacuate to 3-5Pa, introduce ammonia until the vacuum furnace pressure reaches 98-101kPa, the vacuum heating furnace temperature is 450-500℃, keep it for 20-30min, cool it to 200-300℃ with the furnace, keep it for 10-20min, then cool it to 60-80℃ with the furnace and take it out of the furnace to obtain a finished crushing cutter head.

[0029] Note: The quenched crushing cutter head is nitrided to further increase its surface hardness, and then low-temperature tempering is performed to improve the overall toughness of the crushing cutter head.

[0030] The beneficial effects of the present invention are:

[0031] (1) Chromium is an important alloying element in the acid-resistant crushing cutter head prepared by the present invention, which can significantly improve the hardness, strength and corrosion resistance of steel. The carbide formed by chromium and carbon can refine the grains and improve the wear resistance and heat resistance of the material. In stainless steel, the presence of chromium is the key to forming a passivation film, which can protect the steel from further corrosion. Vanadium is a strong carbide-forming element, which can improve the strength and toughness of steel, and also improve the wear resistance and heat resistance of the material. The addition of vanadium helps to stabilize austenite, reduce the risk of intergranular corrosion, and improve the hardenability of steel. Tungsten is an element that improves red hardness and can maintain hardness and strength at high temperatures. Tungsten carbide is very stable and helps to improve the wear resistance and heat resistance of steel. In high-speed tool steel, the addition of tungsten is particularly important because it can provide the required high-temperature performance. Molybdenum can improve the strength and toughness of steel, and also improve the corrosion resistance and heat resistance of the material. The addition of molybdenum helps to stabilize austenite, reduce intergranular corrosion, and improve the hardenability of steel. In high temperature applications, molybdenum can improve the oxidation resistance and creep resistance of steel. Cobalt is an element that improves the wear resistance and corrosion resistance of steel. It can improve the thermal stability of steel and can be used as a hardener in alloy systems in some cases. The addition of cobalt also helps to improve the low temperature toughness of steel. Manganese is an element that improves the strength of steel. It can replace part of nickel and reduce costs. Manganese can also improve the hardenability and wear resistance of steel. In some alloy designs, manganese also helps to reduce the harmful effects of sulfur and form manganese sulfide inclusions, thereby improving the processing properties of steel. Titanium is a stabilizing element that can combine with carbon to reduce the carburization of chromium, thereby maintaining a uniform distribution of chromium in the austenite matrix and improving the overall corrosion resistance of the material. The addition of titanium also helps to inhibit intergranular corrosion, especially in stainless steel containing carbon. Carbon can improve the strength and toughness of steel. Iron is the base material of the alloy. The crystal structure of iron and its interaction with other elements can make other elements closely combine with iron to form a crushing cutter head with high corrosion resistance, high hardness, high strength and high wear resistance.

[0032] (2) The present invention provides three different heat treatment methods, which can further improve the mechanical properties of the crushing cutter head. The surface hardness of the crushing cutter head can be increased by quenching. The toughness of the crushing cutter head can be improved by low-temperature tempering without changing the surface hardness of the crushing cutter head. The nitriding process can further improve the surface hardness and corrosion resistance of the crushing cutter head. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a structural schematic diagram of the crushing cutter head of the present invention.

[0034] Figure 2 yes Figure 1 Cross-section view at AA in the middle.

[0035] Figure 3 It is a schematic diagram of two crushing cutter heads meshing with each other.

[0036] Among them, 1-blade body, 2-tooth cutting edge, 3-meshing groove. DETAILED DESCRIPTION

[0037] Embodiment 1:

[0038] The invention discloses an acid-resistant crushing cutter head for crushing blast furnace titanium slag. The acid-resistant crushing cutter head is composed of the following components in percentage by mass: 12.3% Cr, 5.2% V, 9.1% W, 3.3% Mo, 1.1% Co, 4.5% Mn, 5.2% Ti, 0.5% Si, 0.3% C, and the balance is Fe.

[0039] Embodiment 2:

[0040] The invention discloses an acid-resistant crushing cutter head for crushing blast furnace titanium slag. The acid-resistant crushing cutter head is composed of the following components in percentage by mass: 15.7% Cr, 7.3% V, 10.8% W, 4.0% Mo, 2.5% Co, 5.3% Mn, 6.1% Ti, 0.6% Si, 0.4% C, and the balance is Fe.

[0041] Embodiment 3:

[0042] The invention discloses an acid-resistant crushing cutter head for crushing blast furnace titanium slag. The acid-resistant crushing cutter head is composed of the following components in percentage by mass: 18.7% Cr, 8.4% V, 11.6% W, 5.1% Mo, 3.2% Co, 6.8% Mn, 7.5% Ti, 0.8% Si, 0.5% C, and the balance is Fe.

[0043] As shown in Table 1, comparing Examples 1 to 3, the crushing cutter head prepared by the allocation ratio of each component in Example 3 has the best performance.

[0044] Table 1: Performance comparison of the crushing cutter heads of Example 1 to Example 3:

[0045]

[0046] Embodiment 4:

[0047] like Figure 1 , Figure 2 , Figure 3 As shown, on the basis of Example 3, Example 4 provides a structure of an acid-resistant crushing cutter head, which includes a blade body 1, on which a plurality of tooth cutting edges 2 are integrally formed, and an engagement groove 3 is formed between two adjacent tooth cutting edges 2. The two crushing cutter heads are engaged with each other to crush the titanium slag.

[0048] Embodiment 5:

[0049] Based on Example 4, Example 5 provides a method for preparing an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag, comprising the following steps:

[0050] S1. Sprinkle C powder on the bottom of the crucible, then add Fe blocks, V particles, Cr particles, W powder, Mo powder, Co particles, Mn blocks, Ti particles into the crucible in sequence, then cover the surface of Ti particles with Si powder, and place the crucible in a vacuum melting furnace for vacuum melting;

[0051] S2. The vacuum melting furnace is first evacuated to 3Pa, and then filled with argon until the pressure in the vacuum melting furnace reaches 85kPa, and then the vacuum melting furnace is gradient heated. The temperature of the vacuum melting furnace is now raised to 1700°C, and then maintained for 30 minutes, and then raised to 2600°C and maintained for 20 minutes. After the vacuum melting is completed, a melt is formed;

[0052] S3, introduce the high temperature melt into the crushing knife mold for casting, the casting speed is 8-10cm 3 / s, the melt temperature is 2600℃ at the beginning of casting and 2100℃ at the end of casting. After casting, the mold is naturally cooled to 20℃ and then demoulding is started. At the above casting speed, the alloy formed has less pores and slag, and the casting effect is good. After casting, the crushing knife casting is demoulded after natural cooling;

[0053] S4. Put the crushing knife casting into a vacuum heating furnace for normalizing treatment. The normalizing temperature is 800°C, the normalizing holding time is 20 minutes, the air cooling air temperature is 20°C, and the air flow rate is 3 / s. The above air cooling speed can effectively improve the internal stress of the normalized casting, improve the plasticity and toughness of the material, and make it easier to machine. After the normalizing treatment is completed, air cool to 60°C to obtain a normalized casting;

[0054] S5, fixing the normalized casting on a lathe to perform surface turning on the meshing groove 3 of the normalized casting by turning, and performing surface shoveling on the tooth edge 2 of the normalized casting by a shoveling lathe, and obtaining a crushing cutter head machined part after the shoveling is completed;

[0055] S6. Heat-treating the machined parts of the crushing cutter head, and obtaining a finished crushing cutter head after the heat treatment is completed.

[0056] Heat treatment is to perform surface quenching on the crushing cutter head machine. The specific method of surface quenching is: put the workpiece into a vacuum heating furnace and heat it to 900℃, keep it for 5 minutes, then put the crushing cutter head machined workpiece on the top of the quenching liquid box, rotate the crushing cutter head machined workpiece to quench only the meshing groove 3 and the tooth cutter head, the quenching liquid level is 31cm higher than the meshing groove, the quenching times are 2 times, and the crushing cutter head finished product is obtained after quenching. Through surface quenching, the surface hardness of the tooth edge 2 and the meshing groove 3 is improved without destroying the toughness of other parts of the crushing cutter head, thereby improving the overall strength of the crushing cutter head and avoiding cracks in the blade body during the process of crushing titanium slag.

[0057] The average particle size of Fe block and Mn block is 3cm, the average particle size of V particle, Cr particle, Co particle and Ti particle is 1mm, and the average particle size of W powder, Mo powder, Si powder and C powder is 40μm. Fe block and Mn block have low melting points, which are easy to melt. Larger particle size can reduce cost. The melting points of V particle, Co particle and Ti particle are slightly higher than those of Fe block and Mn block. In order to mix the components evenly, the particle size is smaller than that of Fe block and Mn block. The amount of Si powder added is small, so that it is more evenly distributed in the alloy, so the particle size is selected to be smaller. C powder, W powder and Mo powder have higher melting points, so they are added in the form of powder to make them better distributed in the alloy.

[0058] Embodiment 6:

[0059] Based on Example 4, Example 6 provides a method for preparing an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag, comprising the following steps:

[0060] S1. Sprinkle C powder on the bottom of the crucible, then add Fe blocks, V particles, Cr particles, W powder, Mo powder, Co particles, Mn blocks, Ti particles into the crucible in sequence, then cover the surface of Ti particles with Si powder, and place the crucible in a vacuum melting furnace for vacuum melting;

[0061] S2. The vacuum melting furnace is first evacuated to 4Pa, and then filled with argon until the pressure in the vacuum melting furnace reaches 90kPa, and then the vacuum melting furnace is gradient heated. The temperature of the vacuum melting furnace is now raised to 1900°C, and then maintained for 35 minutes, and then raised to 2700°C and maintained for 25 minutes. After the vacuum melting is completed, a melt is formed;

[0062] S3, the high temperature melt is introduced into the crushing knife mold for casting, and the casting speed is 9.3cm 3 / s, the melt temperature is 2700℃ at the beginning of casting and 2150℃ at the end of casting. After casting, the mold is naturally cooled to 30℃ and then demoulding is started. At the above casting speed, the alloy formed has less pores and slag, and the casting effect is good. After casting, the crushing knife casting is demoulded after natural cooling;

[0063] S4. Put the crushing knife casting into a vacuum heating furnace for normalizing treatment. The normalizing temperature is 850°C, the normalizing holding time is 25 minutes, the air cooling air temperature is 25°C, and the air flow rate is 3.5m / s. The above air cooling speed can effectively improve the internal stress of the normalized casting, improve the plasticity and toughness of the material, and make it easier to machine. After the normalizing treatment is completed, air cool to 65°C to obtain a normalized casting;

[0064] S5, fixing the normalized casting on a lathe to perform surface turning on the meshing groove 3 of the normalized casting by turning, and performing surface shoveling on the tooth edge 2 of the normalized casting by a shoveling lathe, and obtaining a crushing cutter head machined part after the shoveling is completed;

[0065] S6. Heat-treating the machined parts of the crushing cutter head, and obtaining a finished crushing cutter head after the heat treatment is completed.

[0066] Heat treatment is to perform surface quenching on the crushing cutter head machine. The specific method of surface quenching is: put the workpiece into a vacuum heating furnace and heat it to 950℃, keep it for 7 minutes, then put the crushing cutter head machined workpiece on the top of the quenching liquid box, rotate the crushing cutter head machined workpiece to quench only the meshing groove 3 and the tooth cutter head, the quenching liquid level is 31.5cm higher than the meshing groove, the quenching times are 3 times, and the crushing cutter head finished product is obtained after quenching. Through surface quenching, the surface hardness of the tooth edge 2 and the meshing groove 3 is improved without destroying the toughness of other parts of the crushing cutter head, thereby improving the overall strength of the crushing cutter head and avoiding cracks in the blade body during the crushing of titanium slag.

[0067] The average particle size of Fe block and Mn block is 3.3cm, the average particle size of V particle, Cr particle, Co particle and Ti particle is 2.2mm, and the average particle size of W powder, Mo powder, Si powder and C powder is 70μm. Fe block and Mn block have low melting points, which are easy to melt. Larger particle size can reduce cost. The melting points of V particle, Co particle and Ti particle are slightly higher than those of Fe block and Mn block. In order to mix the components evenly, the particle size is smaller than that of Fe block and Mn block. The amount of Si powder added is small, so that it is more evenly distributed in the alloy, so the particle size is selected to be smaller. C powder, W powder and Mo powder have higher melting points, so they are added in the form of powder to make them better distributed in the alloy.

[0068] Embodiment 7:

[0069] Based on Example 4, Example 7 provides a method for preparing an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag, comprising the following steps:

[0070] S1. Sprinkle C powder on the bottom of the crucible, then add Fe blocks, V particles, Cr particles, W powder, Mo powder, Co particles, Mn blocks, Ti particles into the crucible in sequence, then cover the surface of Ti particles with Si powder, and place the crucible in a vacuum melting furnace for vacuum melting;

[0071] S2. The vacuum melting furnace is first evacuated to 5Pa, and then filled with argon until the pressure in the vacuum melting furnace reaches 95kPa, and then the vacuum melting furnace is gradient heated. The temperature of the vacuum melting furnace is now raised to 2000°C, and then maintained for 40min, and then raised to 2800°C and maintained for 30min. After the vacuum melting is completed, a melt is formed;

[0072] S3, the high temperature melt is introduced into the crushing knife mold for casting, and the casting speed is 10cm 3 / s, the melt temperature is 2800℃ at the beginning of casting and 2050℃ at the end of casting. After casting, the mold is naturally cooled to 40℃ and then demoulding begins. At the above casting speed, the alloy formed has less pores and slag, and the casting effect is good. After casting, the crushing knife casting is demoulded after natural cooling;

[0073] S4. Put the crushing knife casting into a vacuum heating furnace for normalizing treatment. The normalizing temperature is 900°C, the normalizing holding time is 35 minutes, the air cooling air temperature is 35°C, and the air flow rate is 4m / s. The above air cooling speed can effectively improve the internal stress of the normalized casting, improve the plasticity and toughness of the material, and make it easier to machine. After the normalizing treatment is completed, air cool to 80°C to obtain a normalized casting;

[0074] S5, fixing the normalized casting on a lathe to perform surface turning on the meshing groove 3 of the normalized casting by turning, and performing surface shoveling on the tooth edge 2 of the normalized casting by a shoveling lathe, and obtaining a crushing cutter head machined part after the shoveling is completed;

[0075] S6. Heat-treating the machined parts of the crushing cutter head, and obtaining a finished crushing cutter head after the heat treatment is completed.

[0076] Heat treatment is to perform surface quenching on the crushing cutter head machine. The specific method of surface quenching is: put the workpiece into a vacuum heating furnace and heat it to 1000℃, keep it for 10 minutes, then put the crushing cutter head machined workpiece on the top of the quenching liquid box, rotate the crushing cutter head machined workpiece to quench only the meshing groove 3 and the tooth cutter head, the quenching liquid level is 32cm higher than the meshing groove, the quenching times are 3 times, and the crushing cutter head finished product is obtained after quenching. Through surface quenching, the surface hardness of the tooth edge 2 and the meshing groove 3 is improved without destroying the toughness of other parts of the crushing cutter head, thereby improving the overall strength of the crushing cutter head and avoiding cracks in the blade body during the process of crushing titanium slag.

[0077] The average particle size of Fe block and Mn block is 5cm, the average particle size of V particle, Cr particle, Co particle and Ti particle is 3mm, and the average particle size of W powder, Mo powder, Si powder and C powder is 80μm. Fe block and Mn block have low melting points, which are easy to melt. Larger particle size can reduce cost. The melting points of V particle, Co particle and Ti particle are slightly higher than those of Fe block and Mn block. In order to mix the components evenly, the particle size is smaller than that of Fe block and Mn block. The amount of Si powder added is small, so that it is more evenly distributed in the alloy, so the particle size is selected to be smaller. C powder, W powder and Mo powder have higher melting points, so they are added in the form of powder to make them better distributed in the alloy.

[0078] As shown in Table 2, by comparing the performance of the prepared crushing cutter heads of Examples 5 to 7, it is found that Example 7 has the best effect.

[0079] Table 2: Performance comparison of the crushing cutter heads prepared in Examples 5 to 7:

[0080]

[0081]

[0082] Embodiment 8:

[0083] Based on Example 7, Example 8 is different from Example 7 in that the heat treatment is to first immerse the crushing cutter head machined parts into quenching, and then perform low-temperature tempering treatment to obtain a finished crushing cutter head. The specific method of immersion quenching is: put the crushing cutter head machined parts into a vacuum heating furnace and heat them to 900°C, keep them for 5 minutes, and then immerse the crushing cutter head machined parts in the quenching liquid for quenching, the quenching times are 2 times, and the quenched crushing cutter head is obtained. This method is to first quench the crushing cutter head as a whole to increase the overall hardness of the blade.

[0084] Low temperature tempering treatment is to put the quenched crushing cutter head into a vacuum heating furnace and heat it to 250℃, keep it for 10 minutes, and then cool it to 60℃ in the furnace to obtain the finished crushing cutter head. Low temperature tempering can improve the overall toughness of the blade and reduce the brittleness of the blade.

[0085] Embodiment 9:

[0086] Based on Example 7, Example 9 is different from Example 7 in that the heat treatment is to first immerse the crushing cutter head machined parts into quenching, and then perform low-temperature tempering treatment to obtain a finished crushing cutter head. The specific method of immersion quenching is: put the crushing cutter head machined parts into a vacuum heating furnace and heat them to 950°C, keep them for 8 minutes, and then immerse the crushing cutter head machined parts in the quenching liquid for quenching, the quenching times are 3 times, and the quenched crushing cutter head is obtained. This method is to first quench the crushing cutter head as a whole to increase the overall hardness of the blade.

[0087] Low temperature tempering treatment is to put the quenched crushing cutter head into a vacuum heating furnace and heat it to 280℃, keep it for 13 minutes, and then cool it to 70℃ in the furnace to obtain the finished crushing cutter head. Low temperature tempering can improve the overall toughness of the blade and reduce the brittleness of the blade.

[0088] Embodiment 10:

[0089] Based on Example 7, Example 10 is different from Example 7 in that the heat treatment is to first immerse the crushing cutter head machined parts into quenching, and then perform low-temperature tempering treatment to obtain a finished crushing cutter head. The specific method of immersion quenching is: put the crushing cutter head machined parts into a vacuum heating furnace and heat them to 1000°C, keep them for 10 minutes, and then immerse the crushing cutter head machined parts in the quenching liquid for quenching, the quenching times are 3 times, and the quenched crushing cutter head is obtained. This method is to first quench the crushing cutter head as a whole to increase the overall hardness of the blade.

[0090] Low temperature tempering treatment is to put the quenched crushing cutter head into a vacuum heating furnace and heat it to 300℃, keep it for 15 minutes, and then cool it to 80℃ in the furnace to obtain the finished crushing cutter head. Low temperature tempering can improve the overall toughness of the blade and reduce the brittleness of the blade.

[0091] By comparing the performance of the crushing cutter heads prepared in Examples 8 to 10, it is found that Example 10 has the best performance.

[0092] Table 3: Performance comparison of the crushing cutter heads prepared in Examples 8-10:

[0093]

[0094] Embodiment 11:

[0095] On the basis of Example 7, Example 11 is different from Example 7 in that, the low-temperature tempering treatment is to put the quenched crushing cutter head into a vacuum heating furnace, evacuate to 3Pa, introduce ammonia until the vacuum furnace pressure reaches 98kPa, and the vacuum heating furnace temperature is 450°C, maintained for 20 minutes, cooled to 200°C with the furnace, maintained for 10 minutes, and then cooled to 60°C with the furnace to obtain a finished crushing cutter head. The quenched crushing cutter head is nitrided to further improve its surface hardness, and then low-temperature tempering is performed to improve the overall toughness of the crushing cutter head.

[0096] Embodiment 12:

[0097] On the basis of Example 7, Example 12 is different from Example 7 in that, the low-temperature tempering treatment is to put the quenched crushing cutter head into a vacuum heating furnace, evacuate to 4Pa, introduce ammonia until the vacuum furnace pressure reaches 100kPa, and the vacuum heating furnace temperature is 480°C, maintained for 25 minutes, cooled to 250°C with the furnace, maintained for 15 minutes, and then cooled to 70°C with the furnace to obtain a finished crushing cutter head. The quenched crushing cutter head is nitrided to further improve its surface hardness, and then low-temperature tempering is performed to improve the overall toughness of the crushing cutter head.

[0098] Embodiment 13:

[0099] On the basis of Example 7, Example 13 is different from Example 7 in that the low-temperature tempering treatment is to put the quenched crushing cutter head into a vacuum heating furnace, evacuate to 5Pa, introduce ammonia until the vacuum furnace pressure reaches 101kPa, and the vacuum heating furnace temperature is 500°C, maintained for 30 minutes, cooled to 300°C with the furnace, maintained for 20 minutes, and then cooled to 80°C with the furnace to obtain a finished crushing cutter head. The quenched crushing cutter head is nitrided to further improve its surface hardness, and then low-temperature tempering is performed to improve the overall toughness of the crushing cutter head.

[0100] As shown in Table 4, by comparing the performance of the crushing cutter heads prepared in Examples 11 to 13, it is found that Example 12 has the best performance.

[0101] Table 4: Performance comparison of the crushing cutter heads prepared in Examples 11 to 13:

[0102]

[0103]

Claims

1. An acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag, characterized in that: The acid-resistant crushing cutter head is composed of the following components in mass percentage: 12.3-18.7% Cr, 5.2-8.4% V, 9.1-11.6% W, 3.3-5.1% Mo, 1.1-3.2% Co, 4.5-6.8% Mn, 5.2-7.5% Ti, 0.5-0.8% Si, 0.3-0.5% C, and the balance is Fe.

2. The acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag according to claim 1, characterized in that: The acid-corrosion-resistant crushing cutter head comprises a cutter body (1), on which a plurality of tooth cutting edges (2) are integrally formed, and an engagement groove (3) is formed between two adjacent tooth cutting edges (2).

3. The method for preparing an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag according to claim 2, characterized in that: The following steps are involved: S1. Sprinkle C powder on the bottom of the crucible, then add Fe blocks, V particles, Cr particles, W powder, Mo powder, Co particles, Mn blocks, Ti particles into the crucible in sequence, then cover the surface of Ti particles with Si powder, and place the crucible in a vacuum melting furnace for vacuum melting; S2. The vacuum melting furnace is first evacuated to 3-5Pa, and then filled with argon until the pressure in the vacuum melting furnace reaches 85-95kPa, and then the vacuum melting furnace is gradient heated. The temperature of the vacuum melting furnace is now raised to 1700-2000℃, and then maintained for 30-40min, and then raised to 2600-2800℃, and maintained for 20-30min. After the vacuum melting is completed, a melt is formed; S3, introducing the high temperature melt into the crushing knife mold for casting, and demoulding after natural cooling after the casting is completed to obtain the crushing knife casting; S4, placing the crushing knife casting into a vacuum heating furnace for normalizing treatment, and air cooling to 60-80° C. after the normalizing treatment to obtain a normalized casting; S5, fixing the normalized casting on a lathe to perform surface turning on the meshing groove (3) of the normalized casting by turning, and performing surface shoveling on the tooth edge (2) of the normalized casting by a shoveling lathe, and obtaining a crushing cutter head machined part after the shoveling is completed; S6. Heat treatment is performed on the machined parts of the crushing cutter head, and a finished crushing cutter head is obtained after the heat treatment is completed.

4. The method for preparing an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag according to claim 3, characterized in that: The average particle size of the Fe block and the Mn block is 3-5 cm, the average particle size of the V particle, the Cr particle, the Co particle, and the Ti particle is 1-3 mm, and the average particle size of the W powder, the Mo powder, the Si powder, and the C powder is 40-80 μm.

5. The method for preparing an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag according to claim 3, characterized in that: The casting speed is 8-10cm 3 / s, the melt temperature is 2600-2800℃ at the beginning of casting and greater than 2000℃ at the end of casting. After casting, the mold is naturally cooled to 20-40℃ and then demoulding begins.

6. The method for preparing an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag according to claim 3, characterized in that: The normalizing temperature is 800-900°C, the normalizing holding time is 20-35 minutes, the air cooling air temperature is 20-35°C, and the air flow rate is 3-4m / s.

7. The method for preparing an acid-corrosion resistant crushing cutter head for crushing blast furnace titanium slag according to claim 3, characterized in that: The heat treatment is to perform surface quenching on the crushing cutter head machine. The specific method of the surface quenching is: put the workpiece into a vacuum heating furnace and heat it to 900-1000°C, keep it for 5-10 minutes, then put the crushing cutter head machined workpiece on the top of the quenching liquid box, rotate the crushing cutter head machined workpiece to quench only the meshing groove (3) and the tooth cutter head, the quenching liquid level is 1-2 cm higher than the meshing groove (3), the quenching times are 2-3 times, and after the quenching is completed, a finished crushing cutter head is obtained.

8. The method for preparing an acid-corrosion resistant crushing cutter head for crushing blast furnace titanium slag according to claim 3, characterized in that: The heat treatment is to first immerse the crushing cutter head machined parts into quenching, and then perform low-temperature tempering treatment to obtain a finished crushing cutter head. The specific method of the immersion quenching is: put the crushing cutter head machined parts into a vacuum heating furnace and heat them to 900-1000°C, keep them for 5-10 minutes, and then immerse the crushing cutter head machined parts in the quenching liquid for quenching. The quenching times are 2-3 times to obtain the quenched crushing cutter head.

9. The method for preparing an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag according to claim 8, characterized in that: The low temperature tempering treatment is to place the quenched crushing cutter head into a vacuum heating furnace and heat it to 250-300° C., keep it for 10-15 minutes, and then cool it to 60-80° C. in the furnace to obtain a finished crushing cutter head.

10. The method for preparing an acid-corrosion-resistant crushing cutter head for crushing blast furnace titanium slag according to claim 8, characterized in that: The low temperature tempering treatment is to place the quenched crushing cutter head into a vacuum heating furnace and heat it to 250-300° C., keep it for 10-15 minutes, and then cool it with the furnace to obtain a finished crushing cutter head.